BASIC CONCEPTS INCLUDED IN THE CONCEPT «ZHAI» (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2025)
This article discusses the main concepts and locative terms associated with the “Zhai» concept, and in some cases their interpretations are proposed. Some concepts related to the concept of “Zhai” are presented in seventeen groups. To achieve the purpose of this article, an attempt was made to group, classify and systematize language units in a specific order. The main sources are encyclopedias, popular science literature, reference books, dictionaries, Internet sites, and other resources used. Also, in this article, some concepts related to the concept of “Zhai” are presented only within seventeen groups, the total number of which is one hundred and eighty-four. Piecing together all the terms relating to different fields of science requires special research, and the authors felt this could not be done within a single paper.
Keywords: academician, hypothesis, concept, cultural studies, political science, rights, sociology, philosophy, futurology.